Old History of Culture and New Cultural History - Norkus, Zenonas (Lietuvos istorijos studijos, 2005)
The article compares two epochs in the history of the Western cultural history writing, with main attention paid to their theoretical assumptions: that of the late 19th - early 20th century (called in the article "old history of culture") and that of the late 20th - early 21st century (known as "new cultural history"). Both of them emerged as challengers: the old history of culture was conceived as the alternative to the once dominant political history, and the new cultural history challenged the social history that dominated in the Western history writing since the 1960s. However, the theoretical sources of their respective concepts of culture are very different. The old history of culture shares its psychologistic, holistic, organicist, and essentialist ideas of culture with the philosophy of culture of the late 19th - early 20th century. New cultural history uses an analytical concept of culture peculiar to contemporary social science as its theoretical point of reference and considers the methods of field research in cultural anthropology as its methodological paradigm. From the analytical point of view (T. Parsons, C. Geertz), culture is an aspect of social reality, represented by the authoritative patterns for action and symbols. This idea of culture invites a historian to consider culture not as a specific set of social phenomena that are concentrated in the particular "cultural institutions" or segment of society, but as an aspect which can be detected in any social phenomena. This idea of culture opens the prospect of the cultural history of politics, cultural history of economy, and so on.